Surface-modified positive electrode material and surface modification method thereof

By depositing a cobalt hydroxide cladding layer on the surface of the positive electrode material, the problem of poor circulation performance of the positive electrode material in the prior art is solved, and higher stability and specific capacity are achieved.

CN119560536AActive Publication Date: 2025-03-04GEM WUXI ENERGY MATERIAL CO LTD

Patent Information

Application Number
CN202411751242.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-04
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

In the prior art, the circulation performance of the coated modified positive electrode material is poor, resulting in low stability and specific capacity.

Method used

The cobalt source is deposited on the graphite sheet by chemical deposition to form a uniform cobalt hydroxide coating layer. Through multiple deposition and the use of alcohol solvents, the loading and distribution uniformity of cobalt hydroxide are improved, and finally the surface-modified cathode material is obtained through sintering.

Benefits of technology

The structural stability and electrochemical activity of the positive electrode material are improved, and the cycle retention rate and specific capacity of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560536A_ABST
    Figure CN119560536A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a surface-modified positive electrode material and a surface modification method thereof. The positive electrode material surface modification method provided by the invention comprises the following steps: S1, mixing a cobalt source with an organic solvent to obtain an intermediate, and depositing the intermediate on a graphite sheet by adopting a chemical deposition method to obtain a coating material; and S2, mixing the positive electrode material with the coating material obtained in the step S1, and calcining to obtain the surface-modified positive electrode material. According to the invention, the cobalt source is deposited on the graphite flake through a chemical deposition method to form the graphite flake of which the surface is uniformly coated with cobalt hydroxide, so that not only can the stability of the coating material structure be improved, but also the electrochemical activity of cobalt hydroxide in the coating material can be further improved; the graphite flake with cobalt hydroxide deposited on the surface is used as a coating material to be sintered with the positive electrode material, so that the obtained surface-modified positive electrode material is good in structural stability and high in specific capacity, and the cycle retention rate of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a surface-modified positive electrode material and a surface modification method thereof. Background Art

[0002] Lithium nickel cobalt manganese ternary materials have become a common positive electrode material for power batteries due to their high energy density, low cost and reliable safety. However, due to factors such as side reactions at the interface between the high nickel material surface and the electrolyte, electrochemical reactions first occurring on the surface during charging and discharging, and mechanical stress during charging and discharging, the positive electrode material will gradually degrade. Currently, most positive electrode materials are coated and modified to form a protective barrier on the surface of the positive electrode material to improve the stability of the positive electrode material. However, the coated and modified positive electrode material often has a low specific capacity problem.

[0003] The prior art discloses a method for preparing a graphene carbon surface modified nickel cobalt manganese oxide ternary positive electrode material, and obtains a positive electrode material with a carbon coating layer, which effectively prevents the reaction between the electrode material and the electrolyte and improves the electrochemical performance of the material. However, the cycle performance of the positive electrode material modified by the carbon coating is poor. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor cycle performance of the positive electrode material after coating and modification in the prior art, thereby providing a surface-modified positive electrode material and a surface modification method thereof.

[0005] On the one hand, the present invention provides a method for surface coating of a positive electrode material, comprising the following steps: S1, mixing a cobalt source with an organic solvent to obtain an intermediate, and depositing the intermediate on a graphite sheet by a chemical deposition method to obtain a coating material; S2, mixing the positive electrode material and the coating material obtained in step S1, and calcining them to obtain a surface-modified positive electrode material.

[0006] In some embodiments, the step of depositing the intermediate on the graphite sheet in step S1 is repeated 2-6 times, preferably 3-5 times.

[0007] In some embodiments, the organic solvent in step S1 includes at least one of an alcohol solvent and dimethyl sulfoxide.

[0008] Preferably, the alcohol solvent comprises a C1-C6 alcohol solvent;

[0009] More preferably, the alcohol solvent includes at least one of ethylene glycol, ethanol and methanol.

[0010] In some embodiments, the cobalt source includes at least one of cobalt acetate, cobalt citrate, and cobalt tartrate.

[0011] In some of these embodiments, the concentration of the cobalt source in the intermediate is 0.04-0.06M.

[0012] In some of the embodiments, the cobalt source and the organic solvent are mixed under ultrasonic conditions, the power of the ultrasound is 38-42 kHz, and the treatment time is 15-60 min.

[0013] In some embodiments, the concentration of the organic solvent is 1.5-5% vol, preferably 1.5-3% vol.

[0014] In some embodiments, the chemical deposition method is a microwave method, the microwave power is 600-1100 W, preferably 700-1000 W, the frequency is 2000-3000 MHz, and the processing time is 30-60 s.

[0015] In some of the embodiments, the ratio of graphite flakes to the mixed liquid is 1:(50-100), and the unit is g:mL.

[0016] In some of the embodiments, in step S2, the mass ratio of the positive electrode material to the coating material is 500:(0.1-3).

[0017] In some embodiments, the mixing step in step S2 includes mixing the positive electrode material and the coating material at a rotation speed of 800-1200 rpm for 2-5 min, then mixing at a rotation speed of 1800-2500 rpm for 2-10 min, and then mixing at a rotation speed of 3500-4500 rpm for 8-20 min.

[0018] In some of the embodiments, the calcination temperature is 400-800° C., and the sintering time is 4-10 h.

[0019] In some embodiments, the chemical formula of the positive electrode material is Li x (Ni a Co b Mn 1-a-b )O2, where 1≤x≤1.05, 0.7≤a≤0.95, 0.01≤b≤0.1.

[0020] On the other hand, the present invention provides a surface-modified positive electrode material, which is obtained by the above-mentioned positive electrode material surface coating method.

[0021] In some embodiments, the particle size of the positive electrode material is 300-400 mesh.

[0022] The technical solution of the present invention has the following advantages:

[0023] The present invention provides a method for surface modification of a positive electrode material, comprising the following steps: S1, mixing a cobalt source with an organic solvent to obtain an intermediate, and depositing the intermediate on a graphite sheet by a chemical deposition method to obtain a coating material; S2, mixing the positive electrode material and the coating material obtained in step S1, and calcining them to obtain a surface-modified positive electrode material. The present invention deposits a cobalt source on a graphite sheet by a chemical deposition method to form a graphite sheet with a surface uniformly coated with cobalt hydroxide. The present invention utilizes cobalt hydroxide and a graphite sheet for synergistic enhancement. On the one hand, the graphite sheet has good electrical conductivity, which promotes charge transfer and improves the electrochemical activity of cobalt hydroxide. On the other hand, the graphite sheet can provide mechanical support for the cobalt hydroxide to avoid agglomeration or degradation of the cobalt hydroxide and reduce its activity during the electrochemical reaction after the battery is formed. Therefore, the composite of the graphite sheet and the cobalt hydroxide can not only improve the stability of the coating material structure, but also further enhance the electrochemical activity of the cobalt hydroxide in the coating material. The graphite sheet with cobalt hydroxide deposited on the surface is used as a coating material and sintered with a positive electrode material to obtain a surface-modified positive electrode material with good structural stability and high specific capacity, and can improve the cycle retention rate of the battery.

[0024] 2. A method for coating the surface of a positive electrode material provided by the present invention, wherein the step of depositing the intermediate on the graphite sheet in step S1 is repeated 2-6 times, preferably 3-5 times. The present invention can achieve uniform distribution of cobalt hydroxide on the surface of the graphite sheet by repeating the deposition times, and can also increase the loading amount of cobalt hydroxide on the graphite sheet, thereby improving the performance of the positive electrode material.

[0025] 3. A method for surface modification of a positive electrode material provided by the present invention, wherein the organic solvent in step S1 comprises at least one of an alcohol solvent and dimethyl sulfoxide. The present invention uses an alcohol solvent or a dimethyl sulfoxide organic solvent, which can form a cobalt source-organic solvent complex when mixed with a cobalt source, which can not only improve the solubility of the cobalt source, but also avoid agglomeration, improve the uniformity of the distribution of cobalt hydroxide on the surface of the graphite sheet, and further improve the stability of the material.

[0026] 4. The present invention provides a method for surface modification of positive electrode materials, wherein the concentration of the organic solvent is 1.5-5% vol, preferably 1.5-3% vol. The present invention uses water to dilute the concentration of the organic solvent, which not only helps to improve the microwave heating efficiency, but also promotes many reactions and improves the quality and stability of the deposit.

[0027] 5. The present invention provides a method for surface modification of a positive electrode material, wherein the chemical deposition method uses a microwave method to coat the surface of a graphite sheet with cobalt hydroxide, and uses microwave energy to promote the interaction between cobalt hydroxide and the graphite sheet, which can promote the interface bonding between cobalt hydroxide and the graphite sheet and improve the stability of the coating material structure. Compared with electrochemical deposition or physical vapor deposition, the microwave deposition method provided by the present invention is simple to operate and can achieve the purpose of optimizing material performance without strict control conditions.

[0028] 6. The present invention provides a method for surface modification of a cathode material, wherein the microwave power is 600-1100 W, preferably 700-1000 W. The present invention limits the microwave power to avoid, on the one hand, too fast chemical reaction rate during the deposition process, local overheating of the reaction area, and too high temperature, which affect the deposition effect; on the other hand, to avoid a slow reaction rate, which leads to low efficiency of the deposition process. By selecting the microwave power of 600-1100 W, preferably 700-1000 W, the reaction rate can be increased, the deposition effect can be ensured, and the stability of the cathode material can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 It is a schematic diagram of the battery cycle performance formed by the surface-modified positive electrode materials prepared in Examples 1-2 and Comparative Example 1 in the experimental examples of the present invention. DETAILED DESCRIPTION

[0031] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0032] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0033] Example 1

[0034] This embodiment provides a method for surface modification of a positive electrode material, and the specific steps and parameters are as follows:

[0035] (1) Cleaning: 6 g of a self-supporting flexible graphite sheet was cleaned with ethanol and deionized water in sequence, and then dried in a vacuum drying oven at 60° C. for 24 h to obtain a clean graphite sheet;

[0036] Preparation of the mixed solution: an ethylene glycol aqueous solution and Co(CH3COO)2 were mixed, and the obtained solution was ultrasonically treated at 40kHz for 30 minutes to obtain a mixed solution, wherein the concentration of Co(CH3COO)2 in the solution was 0.05M, and the concentration of ethylene glycol in the ethylene glycol aqueous solution was 2%vol;

[0037] Microwave deposition: Add clean graphite sheets into 500 mL of the mixed solution and transfer them into a Teflon container for microwave deposition reaction in a microwave oven. The microwave frequency is 2450 MHz, the power is 800 W, and the processing time is 30 s. Take out the graphite sheets deposited with cobalt acetate and put them into cold water for rapid cooling.

[0038] After repeating the microwave deposition step four times, the graphene sheet deposited with Co(OH)2 was gently rinsed with acetone and deionized water in sequence, and then vacuum dried at 60°C for 24 hours to obtain the coated material.

[0039] (2) The lithium source and the ternary precursor are mixed, and then the temperature is first increased to 550°C at a heating rate of 2°C / min in an oxygen atmosphere with a flow rate of 2L / min, and sintered at 550°C for 7h, and then the temperature is increased to 800°C at a heating rate of 2°C / min, and sintered at 800°C for 10h, and finally crushed and passed through a 325-mesh sieve to obtain a sintered product, wherein the lithium source is lithium hydroxide monohydrate, and the ternary precursor is Ni 0.83 Co 0.05 Mn 0.12 (OH)2, the molar ratio of the lithium source to the ternary precursor and the additive is 1:1.02.

[0040] (3) 500 g of the sintered product obtained in step (2) and 1.60 g of the coating material obtained in step (1) were placed in a high-speed mixer, mixed at a speed of 1000 r / min for 2 min, then mixed at a speed of 2000 r / min for 3 min, and finally mixed at a speed of 4000 r / min for 10 min without setting a waiting time in between, to obtain a mixed material;

[0041] Under an oxygen atmosphere, the mixture was heated to 600°C at a heating rate of 2°C / min, sintered at 600°C for 6 hours, naturally cooled to room temperature, and finally passed through a 325-mesh sieve to obtain the positive electrode material of a composite ternary lithium battery.

[0042] Example 2

[0043] This embodiment provides a method for surface modification of a positive electrode material. The specific steps and parameters are the same as those in Embodiment 1, except that the coating material in step (3) is 0.1 g.

[0044] Example 3

[0045] This embodiment provides a method for surface modification of a positive electrode material. The specific steps and parameters are the same as those of Embodiment 1, except that the coating material in step (3) is 3 g.

[0046] Example 4

[0047] This embodiment provides a method for surface modification of a positive electrode material. The specific steps and parameters are the same as those of Embodiment 1, except that the concentration of ethylene glycol in the preparation of the mixed solution in step (1) is 1.5%.

[0048] Example 5

[0049] This embodiment provides a method for surface modification of a positive electrode material. The specific steps and parameters are the same as those of Embodiment 1, except that the concentration of ethylene glycol in the preparation of the mixed solution in step (1) is 3%.

[0050] Example 6

[0051] This embodiment provides a method for surface modification of a positive electrode material. The specific steps and parameters are the same as those of Embodiment 1, except that the concentration of ethylene glycol in the preparation of the mixed solution in step (1) is 5%.

[0052] Example 7

[0053] This embodiment provides a method for surface modification of a cathode material. The specific steps and parameters are the same as those of Embodiment 1, except that the power of the microwave in the microwave deposition step (1) is 700 W.

[0054] Example 8

[0055] This embodiment provides a method for surface modification of a cathode material. The specific steps and parameters are the same as those of Embodiment 1, except that the power of the microwave in the microwave deposition step (1) is 1000 W.

[0056] Example 9

[0057] This embodiment provides a method for surface modification of a cathode material. The specific steps and parameters are the same as those of Embodiment 1, except that the power of the microwave in the microwave deposition step (1) is 600 W.

[0058] Example 10

[0059] This embodiment provides a method for surface modification of a cathode material. The specific steps and parameters are the same as those of Embodiment 1, except that the power of the microwave in the microwave deposition step (1) is 1100 W.

[0060] Embodiment 11

[0061] This embodiment provides a method for surface modification of a cathode material. The specific steps and parameters are the same as those in Embodiment 1, except that the microwave deposition step in step (1) is repeated three times.

[0062] Example 12

[0063] This embodiment provides a method for surface modification of a cathode material. The specific steps and parameters are the same as those in Embodiment 1, except that the microwave deposition step in step (1) is repeated 5 times.

[0064] Embodiment 13

[0065] This embodiment provides a method for surface modification of a cathode material. The specific steps and parameters are the same as those in Embodiment 1, except that the microwave deposition step in step (1) is repeated twice.

[0066] Embodiment 14

[0067] This embodiment provides a method for surface modification of a cathode material. The specific steps and parameters are the same as those in Embodiment 1, except that the microwave deposition step in step (1) is repeated 6 times.

[0068] Embodiment 15

[0069] This embodiment provides a method for surface modification of a positive electrode material, and the specific steps and parameters are as follows:

[0070] (1) Cleaning: 6 g of a self-supporting flexible graphite sheet was cleaned with ethanol and deionized water in sequence, and then dried in a vacuum drying oven at 60° C. for 24 h to obtain a clean graphite sheet;

[0071] Preparation of the mixed solution: a dimethyl sulfoxide aqueous solution and cobalt tartrate are mixed, and the obtained solution is subjected to ultrasonic treatment at 38 kHz for 60 minutes to obtain a mixed solution, wherein the concentration of cobalt tartrate in the solution is 0.04 M, and the concentration of dimethyl sulfoxide in the dimethyl sulfoxide aqueous solution is 2% vol;

[0072] Microwave deposition: Add clean graphite sheets into 600 mL of the mixed solution and transfer them into a Teflon container for microwave deposition reaction in a microwave oven. The microwave frequency is 2000 MHz, the power is 800 W, and the treatment time is 60 s. Take out the graphite sheets deposited with cobalt tartrate and put them into cold water for rapid cooling.

[0073] After repeating the microwave deposition step four times, the graphene sheet deposited with Co(OH)2 was gently rinsed with acetone and deionized water in sequence, and then vacuum dried at 60°C for 24 hours to obtain the coated material.

[0074] (2) The lithium source and the ternary precursor are mixed, and then the temperature is first increased to 550°C at a heating rate of 2°C / min in an oxygen atmosphere with a flow rate of 2L / min, and sintered at 550°C for 7h, and then the temperature is increased to 800°C at a heating rate of 2°C / min, and sintered at 800°C for 10h, and finally crushed and passed through a 325-mesh sieve to obtain a sintered product, wherein the lithium source is lithium hydroxide monohydrate, and the ternary precursor is Ni 0.83 Co 0.05 Mn 0.12 (OH)2, the molar ratio of the lithium source to the ternary precursor and the additive is 1:1.02.

[0075] (3) 500 g of the sintered product obtained in step (2) and 1.6 g of the coating material obtained in step (1) were placed in a high-speed mixer, mixed at a speed of 800 r / min for 5 min, then mixed at a speed of 2500 r / min for 2 min, and finally mixed at a speed of 3500 r / min for 20 min without setting a waiting time in between, to obtain a mixed material;

[0076] In an oxygen atmosphere, the mixture was heated to 400°C at a heating rate of 2°C / min, sintered at 400°C for 10 hours, naturally cooled to room temperature, and finally passed through a 300-mesh sieve to obtain the positive electrode material of a composite ternary lithium battery.

[0077] Example 16

[0078] This embodiment provides a method for surface modification of a positive electrode material, and the specific steps and parameters are as follows:

[0079] (1) Cleaning: 6 g of a self-supporting flexible graphite sheet was cleaned with ethanol and deionized water in sequence, and then dried in a vacuum drying oven at 60° C. for 24 h to obtain a clean graphite sheet;

[0080] Preparation of the mixed solution: the ethanol aqueous solution and cobalt citrate are mixed, and the obtained solution is ultrasonically treated at 42 kHz for 15 minutes to obtain a mixed solution, wherein the concentration of cobalt citrate in the mixed solution is 0.06 M, and the concentration of ethanol in the ethanol aqueous solution is 2% vol;

[0081] Microwave deposition: Add clean graphite sheets into 300 mL of the mixed solution and transfer them into a Teflon container for microwave deposition reaction in a microwave oven. The microwave frequency is 3000 MHz, the power is 800 W, and the treatment time is 30 s. Take out the graphite sheets deposited with cobalt citrate and put them into cold water for rapid cooling.

[0082] After repeating the microwave deposition step four times, the graphene sheet deposited with Co(OH)2 was gently rinsed with acetone and deionized water in sequence, and then vacuum dried at 60°C for 24 hours to obtain the coated material.

[0083] (2) The lithium source and the ternary precursor are mixed, and then the temperature is first increased to 550°C at a heating rate of 2°C / min in an oxygen atmosphere with a flow rate of 2L / min, and sintered at 550°C for 7h, and then the temperature is increased to 800°C at a heating rate of 2°C / min, and sintered at 800°C for 10h, and finally crushed and passed through a 325-mesh sieve to obtain a sintered product, wherein the lithium source is lithium hydroxide monohydrate, and the ternary precursor is Ni 0.83 Co 0.05 Mn 0.12 (OH)2, the molar ratio of the lithium source to the ternary precursor and the additive is 1:1.02.

[0084] (3) 500 g of the sintered product obtained in step (2) and 1.6 g of the coating material obtained in step (1) were placed in a high-speed mixer, mixed at a speed of 1200 r / min for 2 min, then mixed at a speed of 1800 r / min for 10 min, and finally mixed at a speed of 4500 r / min for 8 min without setting a waiting time in between, to obtain a mixed material;

[0085] Under an oxygen atmosphere, the mixture was heated to 800°C at a heating rate of 2°C / min, sintered at 800°C for 4 hours, naturally cooled to room temperature, and finally passed through a 400-mesh sieve to obtain the positive electrode material of a composite ternary lithium battery.

[0086] Comparative Example

[0087] This comparative example provides a method for surface modification of a positive electrode material. The specific steps and parameters are the same as those of Example 1, except that the clean graphite sheet of equal mass in step (1) is used to replace the coating material in step (3).

[0088] Experimental example

[0089] The positive electrode materials prepared in Examples 1-16 and the comparative example were respectively used to prepare button batteries according to the following methods. The specific preparation method is as follows: the positive electrode material: polyvinylidene fluoride: conductive carbon black were homogenized in a mass ratio of 95:3:2, and then the aluminum foil was spread flat on a coating machine for coating (surface density 13.3-13.5 mg / cm 2 , compacted density 3.4-3.6mg / cm 2 ), put it into an 80℃ forced air drying oven and dry it for 3h; then punch, weigh, bake the electrode and make it into a button battery.

[0090] The specific test method of electrochemical performance is to put the button battery into the blue electric test system for electrical performance test, the test voltage range is 2.5-4.25V, the discharge specific capacity of the button battery at different discharge rates and the capacity retention rate of 50 cycles are tested, and the test results are shown in Table 1, and the capacity retention rate of the battery formed by the positive electrode materials prepared in Examples 1-2 and the comparative example at each cycle number within 50 cycles is plotted, see Figure 1 .

[0091] Table 1 Performance test results of button batteries

[0092]

[0093]

[0094]

[0095] According to Table 1 and Figure 1 It can be seen that compared with the positive electrode obtained by coating the graphite sheet as the coating material in the comparative example, the positive electrode material provided by the embodiment of the present invention can significantly improve the discharge specific capacity and capacity retention rate, which proves that the positive electrode material provided by the present invention can improve the electrochemical performance and cycle stability of the positive electrode material.

[0096] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for coating the surface of a positive electrode material, characterized in that: The following steps are included: S1, mixing a cobalt source with an organic solvent to obtain an intermediate, and depositing the intermediate on a graphite sheet by a chemical deposition method to obtain a coating material; S2, mixing the positive electrode material and the coating material obtained in step S1, and calcining to obtain a surface-modified positive electrode material.

2. The method for coating the surface of a positive electrode material according to claim 1, characterized in that: The step of depositing the intermediate on the graphite sheet in step S1 is repeated 2-6 times, preferably 3-5 times; and / or, The organic solvent in step S1 includes at least one of an alcohol solvent and dimethyl sulfoxide; and / or, The cobalt source includes at least one of cobalt acetate, cobalt citrate and cobalt tartrate; and / or, The concentration of the cobalt source in the intermediate is 0.04-0.06M.

3. The method for coating the surface of a positive electrode material according to claim 2, characterized in that: The alcohol solvent includes a C1-C6 alcohol solvent; and / or, Mixing the cobalt source and the organic solvent under ultrasonic conditions, wherein the power of the ultrasound is 38-42 kHz and the treatment time is 15-60 min; and / or, The concentration of the organic solvent is 1.5-5% vol, preferably 1.5-3% vol.

4. The method for coating the surface of a positive electrode material according to claim 3, characterized in that: The chemical deposition method is a microwave method, the microwave power is 600-1100W, preferably 700-1000W, the frequency is 2000-3000MHz, and the processing time is 30-60s; and / or, The alcohol solvent includes at least one of ethylene glycol, ethanol and methanol.

5. The method for coating the surface of a positive electrode material according to claim 4, characterized in that: The ratio of graphite flakes to mixed liquid is 1:(50-100), and the unit is g:mL.

6. The method for coating the surface of a positive electrode material according to claim 5, characterized in that: In step S2, the mass ratio of the positive electrode material to the coating material is 500:(0.1-3): and / or, The mixing step in step S2 includes mixing the positive electrode material and the coating material at a rotation speed of 800-1200 rpm for 2-5 min, then mixing at a rotation speed of 1800-2500 rpm for 2-10 min, and then mixing at a rotation speed of 3500-4500 rpm for 8-20 min.

7. The method for coating the surface of a positive electrode material according to any one of claims 1 to 6, characterized in that: The calcination temperature is 400-800°C and the sintering time is 4-10h.

8. The method for coating the surface of a positive electrode material according to any one of claims 1 to 7, characterized in that: The chemical formula of the positive electrode material is Li x (Ni a Co b Mn 1-a-b )O2, where 1≤x≤1.05, 0.7≤a≤0.95, 0.01≤b≤0.

1.

9. A surface-modified positive electrode material, characterized in that: A positive electrode material obtained by the positive electrode material surface coating method according to any one of claims 1 to 8.

10. The surface-modified positive electrode material according to claim 9, characterized in that: The particle size of the positive electrode material is 300-400 meshes.

Citation Information

Patent Citations

  • Preparation method of positive electrode of lithium-ion secondary battery for electric toothbrush or electric shaver

    CN106532007A

  • Preparation method and application of positive electrode material

    CN115394976A

  • Modified high-nickel ternary positive electrode material and preparation method therefor

    WO2023184996A1

Cited By

  • Positive electrode material and surface coating method thereof

    CN120581554A

  • A positive electrode material and a surface coating method thereof

    CN120581554B